Tinjauan Analisis Percampuran Tempat Jual Beli Produk Halal dan NonHalal Ditinjau Berdasarkan Perspektif Fikih Muamalah dan Hukum Positif - Muhammad Raesyah Jehan Rae; N. Eva Fauziah; Liza Dzulhijjah (Bandung Conference Series: Sharia Economic Law, 2023)
Abstract. This study aims to analyze the practice of mixing and buying and selling halal and non-halal beverage products carried out in one Coffee Shop A business place that is not in accordance with the laws and regulations of Muamalah Jurisprudence in carrying out business practices. The analysis will be reviewed using the perspective of Muamalah Jurisprudence and Positive Law. This research uses descriptive qualitative methods with an empirical normative approach, namely to parse problems based on reality phenomena that occur in the field. The results of research from observations and interviews analyzed by the author found that there are many discrepancies in buying and selling such as selling halal and non-halal products in the same place of business, making between halal and non-halal products is carried out in the same kitchen, mixing production equipment between halal and non-halal products, there is no information that the place sells non-halal products in the form of signs and stickers at the place of business, ignorance of business actors to laws and regulations in running a business. Meanwhile, in the review according to the perspective of muamalah jurisprudence on the practice of mixing and buying and selling halal and non-halal products in one place at Coffee Shop A. Not in accordance with the perspective of muamalah jurisprudence reviewed through the Qur'an, hadith, and ijma.